2016
DOI: 10.1364/oe.24.029843
|View full text |Cite|
|
Sign up to set email alerts
|

Polarization dependence of asymmetric off-resonance long period fiber gratings

Abstract: We present the polarization dependence of strong asymmetric long period fiber gratings written on tapered fibers. We found that for off-resonance conditions the spectral response and the output mode strongly depend on the input state of polarization. We utilize this dependence to obtain a mode selective device and demonstrate radially polarized and azimuthally polarized fiber lasers based on these asymmetric long period fiber gratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…For completeness, we first analyze a simple fiber micro-knot [ 27 ]. We start by tapering a fiber down to a 6 m width over a length of 30–50 mm [ 28 , 29 ]. When a fiber is tapered below 20 m, the light is no longer guided by the core but by the cladding, which leads to an evanescence field outside the fiber.…”
Section: A Simple Micro-knotmentioning
confidence: 99%
“…For completeness, we first analyze a simple fiber micro-knot [ 27 ]. We start by tapering a fiber down to a 6 m width over a length of 30–50 mm [ 28 , 29 ]. When a fiber is tapered below 20 m, the light is no longer guided by the core but by the cladding, which leads to an evanescence field outside the fiber.…”
Section: A Simple Micro-knotmentioning
confidence: 99%
“…We start by tapering a fiber down to a 6 µm width over a length of 30-50 mm [28,29]. When a fiber is tapered below 20 µm, the light is no longer guided by the core but by the cladding, which leads to an evanescence field outside the fiber.…”
Section: A Simple Micro-knotmentioning
confidence: 99%
“…We measured the statistics of ultrafast rogue waves in fiber lasers and found that the underlying mechanism is different than what was previously considered. We will continue to investigate extreme events in different schemes, such as phase locked fiber lasers, 6, 10-13 fiber lasers with unique states of polarization, 14,15 and different types of fiber components [16][17][18][19] We hope to utilize our temporal imaging to focus light through dispersive material and to create rogue waves for high resolution imaging with nano-particles. [20][21][22][23][24][25]…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%